2019
DOI: 10.34117/bjdv5n10-217
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento, caracterização e fitoquímica do óleo essencial de Tetradenia riparia

Abstract: Since ancient times the medicinal plants helped the society's development in order to reach the present resources. The Lamiaceae family is one of the main, containing a large number of species with medicinal potential and Tetradenia riparia is among them. The harvest of T. riparia leaves occurred in the morning at the Universidade Paranaense's medicinal garden, in Umuarama-PR. The extraction of the essential oil (EO) was done by hydrodistillation, the yield was calculated based on the mass of fresh leaves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…According to Souza et al, [51], liver and kidneys are the most sensitive organs to the possible toxic effects of nanoemulsions. The control group (Tween 80) did not show any changes in any organ.…”
Section: Noteo Toxicity To Non-target Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Souza et al, [51], liver and kidneys are the most sensitive organs to the possible toxic effects of nanoemulsions. The control group (Tween 80) did not show any changes in any organ.…”
Section: Noteo Toxicity To Non-target Organismsmentioning
confidence: 99%
“…Scientific studies on both T. riparia essential oil (TrEO) in different parts of the world focused mainly on their chemical composition. TrEO is a complex mixture of terpenoids, including monoterpenes, sesquiterpenes, and diterpenes (hydrocarbons or oxygenated), in which the last one is the most representative class in the oil [7][8][9][10][11]. Studies with TrEO showed it to have antimalarial 2 [12], anti-inflammatory [13], antifungal [14], repellent against Anopheles gambiae [15], trypanocidal [16], anti-tuberculosis [17], and antimicrobial [18,19] activities.…”
Section: Introductionmentioning
confidence: 99%
“…A Lamiaceae é a maior família da ordem Tubiflorae Lamiales, com cerca de 20 a 30 famílias, sendo que quase sua totalidade de espécies tem potencial para ser usada medicinalmente (GONÇALVES et al, 2019). Leonotis nepetifolia é uma espécie pertencente à família Lamiaceae, conhecida popularmente como cordão-de-frade ou cordão-de-São-Francisco a qual é uma espécie considerada medicinal pela medicina Ayurvédica para tratar uma ampla gama de doenças humanas, como tosse, febre, dor de estômago, infecções de pele, reumatismo, calmante, dismenorreia, disfunção renal e inflamações (LI et al, 2012).…”
Section: Introductionunclassified